Respuesta :
We need to put all the xs on one side. We can always move an expression to the other side if we change the sign:
4x-12x=32
now we add up:
-8x=32
divide by 8:
-x=4
multiply by -1:
x=-4, which is the solution
4x-12x=32
now we add up:
-8x=32
divide by 8:
-x=4
multiply by -1:
x=-4, which is the solution
Steps:
1) We have to keep the [tex]x[/tex]'s on one side. For simplification can only occur between [tex]x[/tex] with each other.
2) We have to keep the number on other side. Be careful that you do not simplify it with the [tex]x[/tex].
Simply, group the like terms and simplify.
Methods:
[tex]4x=12x+32[/tex]
=> [tex]4x-12x=12x-12x+32[/tex]
=> [tex]-8x = 0+32[/tex]
=> [tex]-8x=32[/tex]
=> [tex] \frac{-8x}{-8} = -\frac{32}{8} [/tex]
=> [tex]x=-4[/tex]
or, (do side changing)
[tex]4x=12x+32[/tex]
=> [tex]4x-12x=32[/tex]
=> [tex]-8x=32[/tex]
=> [tex]x= \frac{32}{-8} [/tex]
=> [tex]x=-4[/tex]
==================================
HOPE THAT HELPS YOU!! :-)))
1) We have to keep the [tex]x[/tex]'s on one side. For simplification can only occur between [tex]x[/tex] with each other.
2) We have to keep the number on other side. Be careful that you do not simplify it with the [tex]x[/tex].
Simply, group the like terms and simplify.
Methods:
[tex]4x=12x+32[/tex]
=> [tex]4x-12x=12x-12x+32[/tex]
=> [tex]-8x = 0+32[/tex]
=> [tex]-8x=32[/tex]
=> [tex] \frac{-8x}{-8} = -\frac{32}{8} [/tex]
=> [tex]x=-4[/tex]
or, (do side changing)
[tex]4x=12x+32[/tex]
=> [tex]4x-12x=32[/tex]
=> [tex]-8x=32[/tex]
=> [tex]x= \frac{32}{-8} [/tex]
=> [tex]x=-4[/tex]
==================================
HOPE THAT HELPS YOU!! :-)))